1988
DOI: 10.1086/114937
|View full text |Cite
|
Sign up to set email alerts
|

Color and population gradients in the core of the postcollapse globular cluster M30

Abstract: We have developed a new technique for seeking color gradients in multicolor CCD images of a globular cluster. Application of this technique to M30 confirms the radial color gradient reported by others. The B-V and V-R colors show linear gradients, when plotted against log r, that are many times their statistical errors. In the radial range ~ 3-100 arcsec, the B-V and V-R colors increase outwards by about (0.18 + 0.015) mag/dex and (0.09 + 0.01) mag/dex, respectively. Color-magnitude arrays of the central regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
1

Year Published

1991
1991
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 3 publications
4
24
1
Order By: Relevance
“…These measurements are in keeping with earlier observations of M30's central blueing trend (cf. Cordoni & Aurière 1984;Peterson 1986;Piotto et al 1988;Burgarella & Buat 1996). Note, the revised WFPC2 background flux estimates ( § 2.1) result in a color profile that is somewhat different from that published by GWYSB using the same data set, especially for r ∼ > 40 ′′ .…”
Section: Color Profile Of the Cluster Starlightmentioning
confidence: 99%
See 1 more Smart Citation
“…These measurements are in keeping with earlier observations of M30's central blueing trend (cf. Cordoni & Aurière 1984;Peterson 1986;Piotto et al 1988;Burgarella & Buat 1996). Note, the revised WFPC2 background flux estimates ( § 2.1) result in a color profile that is somewhat different from that published by GWYSB using the same data set, especially for r ∼ > 40 ′′ .…”
Section: Color Profile Of the Cluster Starlightmentioning
confidence: 99%
“…Though several authors have shown that central depletion of bright red giant branch (RGB) stars is an important contributor to the color gradient in these clusters (cf. Piotto, King, & Djorgovski 1988;Burgarella & Buat 1996;Guhathakurta et al 1998, hereafter GWYSB), a satisfactory explanation of the underlying physical cause of this RGB depletion has proven elusive (Djorgovski et al 1991). Most globular clusters are well fit by King models (KMs;King 1962) and very few of these show any such color gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Because M30 has a core of high stellar density, we consider the possibility that this environment has influenced the populations of evolved stars in the cluster. M30 has one of the most robustly determined color gradients (approximately linear in log r: ∼ +0.20 mag dex −1 ; Piotto, King, & Djorgovski 1988) of all the globular clusters in the Galaxy. The sense of the color gradient is such that the integrated colors become bluer towards the cluster center.…”
Section: Environmental Effectsmentioning
confidence: 99%
“…Color gradients near the'centers of post core collapse-globular clusters have long been thought to be due to the depletion of the brightest red giants in these very dense environments (Piotto et al 1988). This is quantified by Webster et al (1998) in their detailed investigation of M30's color gradient.…”
Section: Deficiency Of the Brightest Red Giants Near Dense Cluster Cementioning
confidence: 99%